Optical spectroscopy of the Be/black hole binary MWC 656 ‐ interaction of a black hole with a circumstellar disc. Issue 6 (19th July 2022) - Zamanov, Radoslav K.; Stoyanov, Kiril A.; Marchev, Dragomir; Tomov, Nikolay A.; Wolter, Uwe; Bode, Michael F.; Nikolov, Yanko M.; Stefanov, Stefan Y.; Kurtenkov, Alexander; Latev, Georgi Y.
Abstract: We present new spectroscopic observations of the Be/black hole binary MWC 656 obtained during the period 2015–2021. We measure the equivalent width of H α ( EW α ), H β ( EW β $$ EW_{β } $$ ), and the distance between the peaks of H α ( Δ V α $$ Δ V_{α } $$ ), H β ( Δ V β $$ Δ V_{β } $$ ), and FeII ( Δ V FeII $$ Δ V_{FeII} $$ ) lines. Combining new and old data, we find that: (1) the density of the circumstellar disc of MWC 656 ( Δ V α $$ Δ V_{α } $$ versus EW α $$ EW_{α } $$ diagram) is similar to the Be stars. For the Be stars, we find the relation Δ V β = 0.999 Δ V α + 62.4 $$ Δ V_{β }=0.999Δ V_{α }+62.4 $$ km s −1, and the position of MWC 656 corresponds to the average behavior of the Be stars. This means that the presence of the black hole does not change the overall structure of the circumstellar disc; (2) the periodogram analysis indicates modulation of EW α $$ EW_{α } $$ with a period 60.4 ± 0.4 $$ 60.4± 0.4 $$ days, which is identical to the binary orbital period. The maxima of EW α $$ EW_{α } $$ and EW β $$ EW_{β } $$ are around periastron (phase zero); (3) around orbital phase zero, Δ V β $$ Δ V_{β } $$ and Δ V FeII $$ Δ V_{FeII} $$ decrease by about 30 $$ 30 $$ km s −1 . This suggests that we observe an increase of the circumstellar disc size induced by the periastron passage of the black hole and that the entire circumstellar disc pulsates with the orbital period with relative amplitude of 10–20%. The observations also indicate, that the reason for the black hole in MWC 656 to be in deep quiescence is a very low efficiency of accretion ( ∼ 2 × 10 − 6 $$ \sim 2× {10}^{-6} $$ ).